GAYA PENGASUHAN DAN PERKEMBANGAN SOSIAL EMOSI ANAK USIA SEKOLAH PADA KELUARGA PETANI KAYU MANIS - Elmanora, Elmanora; Muflikhati, Istiqlaliyah; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
The aim of the research was to analyze correlation between parenting style and children’s social emotional development, and also to analyze the influence of family characteristics, child characteristics, and parenting style toward school-aged children’s social emotional development in cinnamon farmer families at Tamiai Village, Kerinci District, Jambi Province. This research involved 50 families that were selected randomly. Data collected by interview and self report with questionnaire. Parenting style were measured by emotional coaching instrument and children’s social emotional development were measured by Social Emotional Assets and Resiliency Scales A (SEARS A). Data was analyzed by descriptive, correlation, and regression analysis. The results showed that the mostly parent (34%) applied disapproving parenting style. Index of children’s social emotional development scores were 71,30±10,35. Parenting style was influenced by mother’s education. Laissez faire style correlated negative significant with children’s social emotional development. Children’s social emotional development were influenced by child age.